Pembentukan Karakter Siswa Melalui Pembelajaran Matematika Terintegrasi Islam - Muthia Sarah; M. Imamuddin; Aprianto Aprianto (KOLONI, 2024)
Mathematics is one of the fields of study studied by students in Indonesia. This mathematics has been introduced from kindergarten to university level. Mathematics not only validates numbers, but also teaches humans about structured thinking patterns in solving problems. So this will have an impact on a person's character in their daily life. The aim of this research is to describe changes in student character in the context of mathematics learning that is integrated with Islamic values. Data on changes in student character was obtained by distributing questionnaires to 23 grade 8 students at SMP Negeri 2 Sungai Pua. The results of this research are that students' character can be said to be still not good, looking at the aspect of hard work reaching the highest level of 47.82% or 11 students, while the honest aspect shows the lowest level of 26.08% or only involving 6 students.